Zgodovina slovenskega slovstva I-II Znanstvena izdaja - Štrekelj, Karel (ZRC SAZU, Založba ZRC, 2012)
In the years 1899-1901, Karel Štrekelj (1859-1912) held a course on Slovenian literature at the University of Graz. These are the first university lectures on Slovenian literature in the Slovenian language, published in two volumes. However, Štrekelj's history is more than this: it is a monumental, classically balanced synthesis of all the former knowledge of Slovenian literature, given against rich historical, social, and linguistic backgrounds.It is the first series of university lectures in the Slovenian language on the topic of Slovenian literature. The volumes of manuscript contain a complete overview of Slovenian literature from Brižinski spomeniki (The Freising Manuscripts) to Gregorčič. Štrekelj's lectures are a landmark in the development of Slovenian studies, both from the point of view of university teaching and from the perspective of the fundamental works of Slovenian literary history.